Gender stereotyping, sex and violence in Portuguese and Spanish advertisement - Pereira, Francisco José Costa (2021)
This study analyses the gender stereotypes, sex and violence in advertisements in all me dia except radio, from Portugal and Spain. We have conducted this study after ascertaining that gender stereotypes, as well as sexual and violent scenes, are embedded in advertisement as a formula to increase the possibility of remembering them. This advertisement analysis explores gender stereotyping, sex and violence, both for the Portuguese and Spanish advertisement mar ket. We used a sample of 245 messages from Portuguese and Spanish advertising and a specific grid for this analysis from. We used all media, except radio, between July and November of 2008. The messages were selected from the following categories of products: foods and non-alcohol ic beverages, cars and accessories, restaurants and commercial spaces, financial services and insurance, household products, electronic devices and communications, clothes and alcoholic beverages. These ads messages were select with a criterion of the characters. All messages must have at least one character, male or female. The messages were selected from the following cat egories of products: foods and non-alcoholic beverages, cars and accessories, restaurants and commercial spaces, financial services and insurance, household products, electronic devices and communications, clothes and alcoholic beverages. These ads messages were select with a crite rion of the characters. All messages must have at least one character, male or female. The results in Portugal and Spain about gender stereotypes are in line with previous advertising studies from different countries across the years, showing that it prevails despite the change in women´s role in the world. However, there were practically no situations of discrimination of women or placing them in subordinate roles to men. The results also show us that sex and violence are in a lower level in the advertising of Portugal and Spain. advertising messages from (all) media – Televi sion 83 – Press – 149 – Outdoor 9 – Internet 4. The TV ads were found from 200 hours watched in prime time, (between July and November of 2008 in all broadcast in open signal in Portugal, and Spain, the press ads were found from 300 titles consulted, between July and November of 2008, 22 mensal review, 5 weekly review like, and diary and weekly press, the Internet ads were found from 90 visits to the sites with more visits in Portugal and Spain, between July 2008 and November 2008. Finally the messages from Outdoor came from 50 visits to locations where they were placed between July 2008 and November 2008 in Lisbon and Badajoz.